A Health Decision Support System for Disease Diagnosis based on Machine Learning via Big Data - Subbalakshmi, S; Sumithra, M (International Journal of Computer Sciences and Engineering, 2025)
The usual method of health decision support system through regular database provides less efficient prediction. The analysis accuracy is reduced when the quality of medical data is incomplete. It is replaced by a health decision support system which uses big data and a framework called hadoop. The decision support system is used for implementing the healthcare with the help of Hadoop as it contains large amount of data. Hadoop is used to predict the disease based upon the symptoms. The patients are provided with the unique ID. The Patient’s Health Record (PHR’s) of the patient is stored in the public cloud and is encrypted by homomorphic encryption. When the PHR is needed, they are retrieved from the cloud by decrypting it with the key so, this results in providing the confidentiality to the data. This proposed system provides accurate information and is handy for doctors to diagnose the patients quickly.